Social media usage and interactions: an in-depth interview on BERSIH 2.0 social media visual framing - Shamsiah Abd Kadir,; Mohd Firdauz Mohd Fathir,; Anitawati Mohd Lokman,; Ismail Sualman, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The BERSIH movement in Malaysia is a coalition of civil society organizations advocating for clean and fair elections. This research examines how visual communication shapes political participation by focusing on the visual framing of the BERSIH movement. The study interviewed ten visual communication experts to uncover the meanings and ideological representations behind the visual frames used in the movement. The investigation identified three main themes: portrayal of the crowd, significant individuals, and injustice. The portrayal of the crowd theme highlighted the use of visuals to create a sense of unity and solidarity among participants, while the significant individuals theme emphasized the importance of visual representations of influential figures in shaping people's perceptions. The injustice theme highlighted the use of visuals to expose the injustices and inequality within the electoral system. The study found that visual framing plays a significant role in shaping people's attitudes towards political participation. Neutral or cool visual elements can evoke strong feelings and attract people to the cause, demonstrating that visual elements play a vital role in political mobilization. The findings suggest that carefully crafting visual frames can evoke strong emotional responses and encourage participation in political action. This research sheds light on the power of visual communication in shaping political participation in Malaysia's social movements and highlights the need for a strategic approach in creating visuals that appeal to people's emotions and encourage political engagement.